The knowledge of nursing staff regarding the provision of health care services without the consent of the patient - Augustynek, Ewelina; Jacek, Jacek (Nursing in the 21st Century, 2013)
THE KNOWLEDGE OF NURSING STAFF REGARDING THE PROVISION OF HEALTH CARE SERVICES WITHOUT THE CONSENT OF THE PATIENT Aim. The paper aims to evaluate the knowledge of the nursing staff about providing medical services without patient’s consent. Material and methods. The research used a method of diagnostic survey with questionnaire technique; the research tool was a que stion na i re consisting of 29 questions. The study material comprised responses of 300 respondents employed at the Department of Internal Diseases, Surgery, Urology and Psychiatry at stationary health care institutions of the Podkarpacki region. Results. Over 3/4 of respondents are aware of the obligation to provide help in emergency cases of life threat, serious detriment to health in accordance with their professional qualifications. The knowledge of nursing staff on the legal regulations being in force concerning some other aspects of professional practice is insufficient. Conclusions. Knowledge of the legal bases is the basis in everyday medical practice of nursing staff. A sense of professional responsibility for the health of the patient obliges the nursing staff for continuous professional development.